The Effect of Financial Ratios on the Operational Performance of Logistics Companies In PT The Eternal Universe of Sentosa - Yovika Septiana; Thomas Sidharta (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of financial ratios, consisting of Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Return on Assets (ROA), on the operational performance of PT. Semesta Langgeng Sentosa during the 2021–2024 period. A quantitative approach was employed using documentation methods and field studies to obtain secondary data from the company’s financial reports. The data were analyzed using multiple linear regression, preceded by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, to ensure the model’s validity and reliability. Operational performance was measured using asset turnover ratios and annual productivity levels. The results show that CR, TATO, and ROA have a positive and significant effect on operational performance, while DER has a negative but significant influence. These findings indicate that strengthening liquidity, increasing asset utilization efficiency, and enhancing profitability contribute positively to improving operational efficiency in logistics companies. Conversely, a high debt structure may hinder the achievement of optimal performance. This research provides theoretical contributions to the development of financial management and accounting knowledge, especially in the context of private logistics companies. Practically, the results can serve as a strategic reference for company management in evaluating internal financial conditions and formulating data-driven decisions to improve operational performance continuously and sustainably.